2007
DOI: 10.2807/esm.12.12.00751-en
|View full text |Cite
|
Sign up to set email alerts
|

The burden of infectious diseases in Europe: a pilot study

Abstract: The main objectives of this pilot study were to test the potential use of the disease burden concept in the field of infectious diseases, including data quality and availability; to recommend future studies; and to stimulate a debate. The disease burden of seven infectious diseases (influenza, measles, HIV, campylobacteriosis, infection with enterohaemorrhagic Escherichia coli, salmonellosis and tuberculosis) in Europe was estimated by calculating Disability Adjusted Life Years (DALYs), a composite measure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 43 publications
0
69
0
7
Order By: Relevance
“…Providing joint TB and HIV management for more patients in countries already burdened by drug-resistant TB will present a formidable challenge. While, with some exceptions, TB mortality rates in the EU are low, a recent study showed that TB still contributes heavily to death from infectious diseases in 12 EU countries in which the mean number of reported TB deaths in 2003-2004 was twice as high as that attributed to HIV infection [5].…”
Section: Resultsmentioning
confidence: 99%
“…Providing joint TB and HIV management for more patients in countries already burdened by drug-resistant TB will present a formidable challenge. While, with some exceptions, TB mortality rates in the EU are low, a recent study showed that TB still contributes heavily to death from infectious diseases in 12 EU countries in which the mean number of reported TB deaths in 2003-2004 was twice as high as that attributed to HIV infection [5].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore a three-month pilot study to explore the potential of the disease burden concept for seven communicable diseases was conducted [18].…”
Section: Collaboration With the Ecdcmentioning
confidence: 99%
“…In addition, three reports from the National Institute for Public Health and the Environment in the Netherlands (RIVM) have been included Mangen et al, 2014;Van Lier et al, 2007).…”
Section: Disease Burden Methodsmentioning
confidence: 99%
“…For foodborne infections for which reporting is mandatory, modelling of underreporting is often used to estimate the 'true number' of infections in the population Mangen et al, 2014;Van Lier et al, 2007). Food attribution modelling can be used to attribute chemical hazard or pathogen specific illnesses to specific foods, food categories or major transmission pathways.…”
mentioning
confidence: 99%